2022
DOI: 10.1039/d2ta03145k
|View full text |Cite
|
Sign up to set email alerts
|

A Li+ and PANI co-intercalation strategy for hydrated V2O5 to enhance zinc ion storage performance

Abstract: Layered vanadium-based oxides are regarded as promising cathode material for zinc-ion batteries (ZIBs), due to their open-framework crystal structure and high theoretical specific capacity. However, the sluggish Zn2+ diffusion and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…However, like the V 2 O 5 cathode, the CVO cathode also showed a rapid capacity decay, which was mainly due to the irreversible structural deterioration of the host material caused by the repeated insertion/extraction of Zn 2+ , eventually resulting in the collapse of the structure and capacity attenuation. 26 In contrast, the CPVO cathode not only exhibited the highest discharge capacity of 498.5 mA h g −1 at 0.1 A g −1 but also possessed the optimal cycling stability (98.9% capacity retention over 100 cycles), which may be associated with the abundant electrochemical active sites and fast Zn 2+ diffusion kinetics of the CPVO nanosheets. Meanwhile, the co-intercalation of Ce ions and PANI could effectively buffer the large volume variation and alleviate the collapse and dissolution of the host structure, thereby achieving excellent Zn 2+ storage performance.…”
Section: Electrochemical Performancementioning
confidence: 93%
See 1 more Smart Citation
“…However, like the V 2 O 5 cathode, the CVO cathode also showed a rapid capacity decay, which was mainly due to the irreversible structural deterioration of the host material caused by the repeated insertion/extraction of Zn 2+ , eventually resulting in the collapse of the structure and capacity attenuation. 26 In contrast, the CPVO cathode not only exhibited the highest discharge capacity of 498.5 mA h g −1 at 0.1 A g −1 but also possessed the optimal cycling stability (98.9% capacity retention over 100 cycles), which may be associated with the abundant electrochemical active sites and fast Zn 2+ diffusion kinetics of the CPVO nanosheets. Meanwhile, the co-intercalation of Ce ions and PANI could effectively buffer the large volume variation and alleviate the collapse and dissolution of the host structure, thereby achieving excellent Zn 2+ storage performance.…”
Section: Electrochemical Performancementioning
confidence: 93%
“…25 Although these methods have achieved encouraging achievements, the guest ions inserted into the V 2 O 5 electrode tend to exhibit poor electronic conductivity, leading to unsatisfactory Zn 2+ diffusion kinetics. 26 In addition, the strong electrostatic interaction between divalent Zn 2+ and the host structure inevitably hinders the intercalation/deintercalation behavior, resulting in limited Zn 2+ storage performance. 27 Recent reports have suggested that the intercalation of conducting polymers (e.g., polyaniline, polypyrrole and poly (3,4-ethylenedioxythiophene)) in the V 2 O 5 framework can signicantly expand its layer spacing and weaken the electrostatic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of a La-V 2 O 5 : In the La-V 2 O 5 synthesis procedure, [44,80] 0.364 g V 2 O 5 and 0.130 g La(NO 3 ) 3 were dissolved in 50 mL deionized water. After stirring at 40 °C for 10 min, 2 mL H 2 O 2 was instilled into the above slurry.…”
Section: Methodsmentioning
confidence: 99%
“…However, the metal ions inserted V 2 O 5 electrodes often suffer from poor electronic conductivity. [ 15,16 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, the metal ions inserted V 2 O 5 electrodes often suffer from poor electronic conductivity. [15,16] Guest species must be considered to realize stable structure, fast charge transfer and reversible migration of Zn 2+ in the layered structure during the charge/discharge process. The organic ions, which could develop weak interaction with Zn 2+ , were also introduced into layered cathode materials to boost the zinc-storage properties.…”
Section: Introductionmentioning
confidence: 99%